2023
DOI: 10.3390/jcm12062215
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in People with Multiple Sclerosis: The Role of Disease Severity, Illness Perception, and Depression

Abstract: Despite being a common issue in people with multiple sclerosis (pwMS), sexual dysfunction is still underinvestigated. This work aims to assess the potential determinants of sexual dysfunction in pwMS by considering its relationship with disease severity (in terms of global disability), illness perception, and depressive symptoms. In this multicenter study, 1010 pwMS responded to an online survey. A serial mediation model considering negative illness perception and depressive symptoms as mediators of the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The results of the current study revealed that the sperm count and viability percentage, as well as total and progressive motility percentages, were significantly decreased following chronic demyelination and even 5 wk of CPZ withdrawal in the C57/BL 6 mouse model. However, despite sexual dysfunctions being one of the common complaints of MS individuals (28), because of various items like considering sexual deficits as a secondary symptom (3), these issues are highly underdiagnosed (29) and mostly under-investigated (9). Concerning the deteriorative consequences of demyelination on endocrine/sexual and fertility issues, more experimental and clinical investigations should consider these complications in MS individuals (30).…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study revealed that the sperm count and viability percentage, as well as total and progressive motility percentages, were significantly decreased following chronic demyelination and even 5 wk of CPZ withdrawal in the C57/BL 6 mouse model. However, despite sexual dysfunctions being one of the common complaints of MS individuals (28), because of various items like considering sexual deficits as a secondary symptom (3), these issues are highly underdiagnosed (29) and mostly under-investigated (9). Concerning the deteriorative consequences of demyelination on endocrine/sexual and fertility issues, more experimental and clinical investigations should consider these complications in MS individuals (30).…”
Section: Neuroimagingmentioning
confidence: 99%
“…Although hormonal and sexual disorders are common symptoms in many neurological diseases (8), due to several factors like the complex nature of these symptoms and the influence of other symptoms, sexual and fertility issues are an MS individual challenge that needs more attention and investigation (9). Several hormonal disturbances are the main culprits of men's fertility rate impairment.…”
Section: Introductionmentioning
confidence: 99%